Sistem Pertanian Padi “Sipadi” Rice Farming System As a Web-Based Agricultural Business Development Technology - Vella Yulitsa Tri Bawana (LPPM Universitas Mercu Buana Yogyakarta, 2021)
Blitar Regency is one of the producers of agricultural commodities. Agricultural products in the Blitar Regency are quite stable because geographic areas that are considered to have fertile soil and their people have traditionally carried out agricultural activities from an early age can produce abundant agricultural products and can meet the needs of the community with these agricultural products. However, it is not uncommon for farmers to receive yields that tend to rise and fall unstably due to the season and also pests on agricultural products, especially rice. This study aims to assist farmers, especially rice farmers in determining the process of land management, selection of seeds or rice seeds, rice care, pest classification, harvesting, inventors, and turnover or profit estimates. This research uses a qualitative method with a descriptive approach. Data collection used by researchers is by means of surveys, interviews, observations, and secondary data and documentation as supporting research, and using Backtracking Algorithms. In the application that we make is very helpful for farmers, especially in Blitar Regency.